Composition of a plan of an architectural complex = Kompozycja planu zespołu architektonicznego - Maryńczuk, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It may be proved that the space should be composed in a certain and not other manner for specific needs and objectives so that its form was not accidental. The composition is a very important part of creation - the knowledge of its rules (following them or their intentional violation) conditions the success of each project.
Keywords: zespół architektoniczny; kompozycja przestrzenna; elementy kompozycji; plan urbanistyczny; plane composition; plane surface; principles; design